Differentiation of dural arteriovenous fistula from reflux venous flow on 3D TOF-MR angiography: identifying asymmetric enlargement of external carotid artery branches. Issue 9 (September 2020) - Lee, J.; Lee, J.Y.; Lee, Y.-J.; Park, D.W.; Kim, T.Y.; Kim, Y.S.; Kim, H.Y.
Abstract : AIM: To differentiate dural arteriovenous fistula (DAVF) from reflux venous flow (RVF) by assessment of asymmetric enlargement of external carotid artery (ECA) branches on three-dimensional (3D) time-of-flight magnetic resonance angiography (TOF-MRA). MATERIALS AND METHODS: Nineteen patients with DAVF and 27 patients with RVF were included from September 2007 to April 2019. The locations of DAVF were the cavernous ( n =9) and sigmoid-transverse ( n =6) sinuses, and the jugular ( n =3) and sphenoparietal ( n =1) veins. Two radiologists visually assessed asymmetric enlargement of the ascending pharyngeal artery (ASP), middle meningeal artery (MMA), accessory meningeal artery (AMA), artery of the foramen rotundum, and occipital artery. MMA size was also measured quantitatively. RESULTS: More frequent asymmetric enlargement of the ASP and MMA were seen in DAVF than in RVF (17 of 19 versus 3 of 27 for ASP; 16 of 19 versus 1 of 27 for MMA, p <0.01). The AMA, artery of the foramen rotundum, and occipital arteries were not visualised in RVF patients. The ipsilateral MMA size was significantly larger in DAVF than in RVF (2.14 versus 0.64 mm 2, p < 0.01). The diagnostic performance of ipsilateral MMA size for DAVF was good, with an area under the receiver operating characteristic curve of 0.89, with a sensitivity of 84.2% and a specificity of 81.5% at a cut-off of 1.08 mm 2 . CONCLUSIONS: DAVF showed significantly larger ECA branches than RVF on 3D TOF-MRA. Therefore, thorough evaluation of ECA branches could help to differentiate DAVF from RVF. Highlights: Dural AVF can show asymmetric enlargement of feeding arteries on 3D TOF-MRA. The common feeders include ascending pharyngeal, middle meningeal, and occipital arteries. Reflux venous flow (RVF) does not show asymmetric enlargement of ECA branches. Analysis of ECA branches could be helpful for differentiating dural AVF from RVF.